The Effect of Lead (Pb) Content on the Number of Stomata on Tabebuia aurea Leaves in Surabaya City - Hamidah, Hamidah; Chrisetioningsih, Nadia Immanuela; Wibowo, Anjar Tri (Syntax Literate, 2024)
This study aimed to investigate the impact of lead (Pb) content on stomatal density in Tabebuia aurea leaves across various locations in Surabaya. Samples were collected from three distinct areas with different traffic densities: Campus C of Universitas Airlangga, Menur Road, and Prapen Road. Lead (Pb) content was analyzed using atomic absorption spectroscopy (AAS). The results revealed that the average lead (Pb) content absorbed by Tabebuia aurea leaves due to vehicle emissions was 1.06 mg/kg at Campus C, 1.78 mg/kg at Menur Road, and 2.35 mg/kg at Prapen Road. Stomatal density in Tabebuia aurea leaves was found to be 119.25 ± 3.605 stomata/mm² at Campus C, 123.88 ± 1.000 stomata/mm² at Menur Road, and 140.92 ± 7.211 stomata/mm² at Prapen Road. These findings suggest that stomatal density in Tabebuia aurea leaves is lower on Menur Road compared to Prapen Road but higher than at Campus C. This indicates a positive correlation between stomatal density and lead (Pb) content in Tabebuia aurea leaves.